Coronal lumbar horizontal shift and lower limb force line in patients with knee osteoarthritis: a correlation study - Zhang, Yong-Wang; Du, Pei-Yu; Li, Xi; Liu, Lu; Yan, Yun-Tao; Bai, Yi-Cong; Tian, Xin-Yu; Du, Shuang-Qing (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectiveThe aim of this study is to explore the correlation between the horizontal deviation of the coronal lumbar spine and the lower limb force line in knee osteoarthritis (KOA).MethodsA retrospective analysis of 233 KOA cases (47 male patients and 186 female patients, aged 50–83 years, with an average of 61.55 ± 8.72 years) admitted from 1 October 2022 to 31 December 2023 was conducted. Bilateral hip, knee, and ankle (HKA) angles; mechanical axis offset distance (MAD); joint line convergence angle (JLCA); lumbar–knee offset distance (LKOD, a self-tested angle reflecting the difference in the position of the bilateral knee joint relative to the lumbar vertebra); Western Ontario and McMaster Universities Arthritis Index (WOMAC) score; and baseline data records were assessed for all patients.ResultsThe WOMAC score was correlated with L1, L2, and L3 in LKOD (P < 0.05; r = 0.240, 0.362, and 0.386) but not with L4 and L5 (P > 0.05). WOMAC was also associated with HKA, MAD, and JLCA on the affected side (P < 0.05; r = −0.127, 0.140, and 0.135). The unaffected side and d-values were not associated with HKA, MAD, and JLCA (the d-value represents the absolute value of the difference between the unaffected and affected sides, which represents the overall change in both lower limbs) (P > 0.05). L1–L5 in LKOD was associated with HKA and MAD d-values (P < 0.05); LKOD was not correlated with HKA, MAD, and JLCA on the affected side.ConclusionLumbar horizontal deviation is a risk factor affecting all angles in both lower limbs and may aggravate knee bone and joint symptoms. The influence of horizontal direction changes in the lumbar spine on KOA, especially change in L3, should be prioritized in the clinical treatment and research of KOA.